The Effects of International Financial Integration in a Model with Heterogeneous Firms and Credit Frictions - Maik Heinemann; Christiane Clemens (Verein für Socialpolitik, 2010)
This paper examines the pattern of international capital flows in a two-sector dynamic general equilibrium heterogeneous agent model with financial frictions and idiosyncratic entrepreneurial risk. Countries differ only with respect to the tightness of constraints on the domestic credit market. The results provide an explanation for the 'Lucas paradox', i.e., the empirical observation of capital flowing from poor to rich countries, where lending countries are characterized by tighter domestic constraints. International integration only indirectly mitigates negative output and welfare effects from financial constraints on domestic credit markets. The effects are triggered by adjustments in the real interest rate to global real return. We observe an accumulation-driven rise in the entrepreneurship rate and positive output effects for countries with relatively tight constraints who generally benefit from financial integration. The macroeconomic effects can be adverse for the capital-importing country which may suffer from a decrease in GNP in the integrated economy. The model is calibrated to match standard macro data, entrepreneurship rates, and Gini coefficients from OECD countries.
Keywords: C68; D91; F41; 330; DSGE; financial constraints; financial market integration; international capital flows; heterogeneous agents; occupational choice